Young Children's Positive and Negative Parasocial Relationships with Media Characters. Issue 2 (2nd April 2016) - Jennings, Nancy; Alper, Meryl
Abstract : There is a scarcity of research on how young children form short- and long-term emotional connections with popular media characters. Preexisting research on young children's parasocial relationships (PSR) with media personae has traditionally operationally defined PSR exclusively in terms of friendship and focused on television characters. However, a growing body of research suggests the need for a wider survey of children's media platforms. Scholarship also actually points to two distinct constructs of PSR: positive PSR (friendly feelings or amicability) and negative PSR (unfriendly feelings or antipathy). This study engaged 88 children ages 5–7 in open- and closed-ended questions designed to measure both positive and negative PSR. Our research reveals a more nuanced understanding of young children's PSR.